Gender Empowerment and Women’s Socioeconomic Conditions as Predictors of Poverty: Evidence from Indonesia’s Panel Data (2020–2024) - Muhammad Rizqon Thoyyiba; Muhammad Jimmy Saputra; Muhammad Azkaa Al Atqiaa; Muhammad Haqin Nazili; Al Hujjah Asianingrum; Nur Salam (JISPO : Jurnal Ilmu Sosial dan Ilmu Politik, 2025)
This study examines whether gender empowerment and women’s socioeconomic conditions help explain poverty variation in Indonesia during 2020–2024, a period when persistent poverty reduction efforts coincided with continuing gender gaps in education, work, and economic decision-making. The study aims to estimate the effects of the Gender Empowerment Index (GEI), women’s average years of schooling (AYSW), the female labour force participation rate (FLFPR), and women’s revenue contribution (RCW) on the percentage of poor population (P0). Using balanced provincial panel data, panel regression was applied and model selection tests (Chow, Hausman, and Lagrange Multiplier) indicated that the Random Effects Model is the most appropriate specification. The results show that GEI and AYSW have significant negative associations with poverty, implying that stronger empowerment and higher female educational attainment are linked to lower poverty rates across provinces. In contrast, RCW has a positive and significant association with poverty, suggesting that a higher female income ratio may reflect structural vulnerability (such as declining male earnings or low-quality, distress-driven work) rather than improved household welfare. FLFPR is negative but not statistically significant, indicating that participation alone does not necessarily reduce poverty without adequate job quality and earnings. Overall, the study concludes that gender empowerment and women’s education are key levers for poverty reduction, while labour-market indicators require more nuanced interpretation. This research contributes recent provincial evidence on gender–poverty linkages and underscores policy implications for expanding women’s education, strengthening empowerment, and promoting decent work conditions rather than focusing solely on participation rates.